Elsbeth. Season two [videorecording (DVD)] - King, Robert (Screenwriter); King, Michelle (Television producer) (CBS Studios Inc., 2025)
Elsbeth Tascioni, the astute but unconventional consent decree attorney working with the NYPD to catch New York's most well-heeled murderers utilizing her unique point of view. Season two of the critically acclaimed series brings new cases and challenges when mistakes of the past come back to haunt Elsbeth, her boss Captain Wagner, and detective in training Officer Kaya Blanke.